Developing a National Approach to Business Change in Welsh Local Government - Gary Walpole (2009)
Overview1.1 CRG Research Ltd, in association with the LEED1 Unit at Cardiff Business School were commissioned by the Welsh Assembly Government to undertake research into ‘Developing a National Approach to Business Change in Welsh Local Government.’1.2 The research commenced in May 2008, with the following aims:• Stage 1: to compile a body of work on which Welsh local authorities (and the public sector more widely) can draw to identify the appropriate business change methodologies for their specific project.• Stage 2: to conduct primary research to provide a core resource setting out the current levels of business change activity and expertise that exists in the Welsh local government community.• Stage 3: to summarise the information collected during Stage 2 and use that to make recommendations as to how these resources might be used to drive future business change projects in local government in a way that develops the in-house skills base and mechanisms for knowledge transfer within and between authorities.1.3 More specific objectives were to:• Review the recent academic literature and generate a single source of information about what business change methodologies might be applicable and appropriate to public sector organisations;• Develop an analysis of the range of business change skills in Welsh local authorities including how that has been shaped by the need to drive service improvements for the citizen;• Make recommendations as to how to develop a core set of business change expertise in Welsh local authorities that can form the basis of a shared and universally available resource, including what action the Assembly Government might take at a national level to improve the capacity, capability and skills transfer into and between local authorities.1 Leadership, Enterprise and Economic Development 1